The relevance of pharmacological neuroenhancement for stress and resilience—A multistudy report - Darwig, Julia; Gaum, Petra Maria; Pauli, Roman; Nassri, Lina; Lang, Jessica (Frontiers in Public Health, 2022)
Background Pharmacological neuroenhancement (PNE) is discussed as coping strategy in academic and work-related contexts. Depending on the definition of PNE and sample population, different prevalence rates for various groups have been reported. In the three parts of the study, prevalence rates for work and student populations in Germany are detected and the reasons for PNE and possible causal associations between PNE, stress and resilience are investigated. Methods In part 1 of the study, 152 occupational physicians (OPs) were surveyed about prevalence rates and reasons for PNE. In part 2 of the study, 1,077 German students reported on their PNE behavior. 704 students were then longitudinally considered to draw conclusions on causal associations between PNE, stress, and resilience. Results The OPs' estimated prevalence rate of 10.9% in a working population is higher than the prevalence rate of 5.4% for prescription and illicit substances found in the student sample in part 2 of the study. The reason suspected by OPs to be most important for PNE with prescription drugs were performance pressure and long working hours. Using soft enhancers, such as caffeine, is most common with a prevalence rate of 76.8% in the student sample. Stress predicts a higher (β = 0.179, p < 0.001) and resilience a lower use of PNE (β = −0.13, p = 0.001). Resilience predicts a lower (β = −0.35, p < 0.001) and PNE a higher level of stress (β = 0.11, p < 0.001). Conclusion OPs suspect a prevalence rate of 10.9% among the working population, while we found a prevalence rate of 5.4% among students. Caffeine is the most used substance for PNE, while the use of prescription and illicit substances remains low. Higher levels of stress and lower levels of resilience result in a higher use of PNE. Universities should therefore include the promotion of resilience and methods for dealing with study stress in health programs to reduce PNE.